Risk of CIN3 or worse with persistence of 13 individual oncogenic HPV types. Issue 8 (10th January 2019) - Sand, Freja Lærke; Munk, Christian; Frederiksen, Kirsten; Junge, Jette; Iftner, Thomas; Dehlendorff, Christian; Kjaer, Susanne K.
Abstract : Human papillomavirus (HPV) is essential in cervical carcinogenesis, however, less is known about the carcinogenic potential of individual HPV types. Our aim was to examine the risk of cervical intraepithelial neoplasia grade 3 or worse (CIN3+) after persistence of 13 individual oncogenic HPV types. Liquid‐based cervical samples (n = 40, 399) collected in 2002–2005 were tested for HPV by hybrid capture 2 and genotyped with INNO‐LiPAv2. Persistence was defined as having the same genotype twice 1–4.5 years apart. The absolute risk of CIN3+ was estimated by the Aalen‐Johansen estimator and Cox proportional hazard regression was used to compare the rates of CIN3+ according to HPV type adjusting for age and time between HPV tests. Of 2, 875 oncogenic HPV‐positive women, 874 had persistence of one or more types and 761 persisted for one oncogenic HPV type only. Persistent HPV16 infection was associated with the highest risk of CIN3+, with an 8‐year absolute risk of 55% (95% CI: 45%–66%), followed by HPV33 (33% (95% CI: 20%–50%)), HPV18 (32% (95% CI: 20%–48%)) and HPV31 (31% (95% CI: 21%–46%)). Other HPV types, including HPV52 and HPV45, were also associated with high risks. Persistent HPV56 had the lowest 8‐year absolute risk of CIN3+ (3% (95% CI: 0.4%–20%)). In Cox analyses, a similar pattern remained after adjustment for age and time between tests. Our results add knowledge about the varying carcinogenic potential of individual persistent oncogenic HPV types, which may have implications for the clinical use of HPV testing. Abstract : What's new? While the critical role of human papilloma virus (HPV) infection in cervical cancer is well established, less is known about the cancer risk associated with individual HPV subtypes. Here the authors performed a large population‐based study including 40, 000 Danish women. They show large differences in absolute risk for high‐grade cervical intraepithelial neoplasia (CIN3+) development linked to persistent infection with 13 oncogenic HPV types. They suggest that these differences may inform clinical use of type‐specific HPV testing in the future.